MEASUREMENT OF VISCOSITY AND SUCROSE CONCENTRATION IN AQUEOUS SOLUTION USING PORTABLE BRIX METER - Hidayanto, Eko; Tanabe, Teruo; Kawai, Jun (BERKALA FISIKA, 2010)
The viscosity of aqueous sucrose solution in various concentrations and the sugar content were measured by using an Ostwald viscometer and a commercial available of portable Brix meter respectively. The increasing of the concentration of sucrose would also followed by increasing viscosity of the solution. Depending on their concentration, the measured value of viscosity of solution would be automatically confirmed into the desired concentration unit. The suitability of Brix meter for other application will be checked.